DAMPAK FASILITAS BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR GAMBAR TEKNIK SELAMA MASA PANDEMI COVID-19 - Nurcholish Arifin Handoyono (Jurnal Pendidikan (Teori dan Praktik), 2022)
The technical drawing learning outcomes of students of SMK Piri 1 Yogyakarta tend to decline. This happened because the online learning process was not optimal during the COVID-19 epidemic. Learning technical drawing online there are still limited learning facilities at home for each student. This will also have an impact on student motivation to learn below. This research reveals the impact of learning facilities and learning motivation on the technical drawing learning outcomes in online learning. The research was conducted at SMK Piri 1 Yogyakarta in the even semester of the 2019/2020 academic year. The research population was students of class X TKR. The study used saturated sampling, where all members of the population were sampled, totaling 51 students. Data collection techniques used questionnaires and documentation. The data analysis technique used descriptive statistics, the prerequisite analysis used the normality test, linearity, and multicollinearity; and hypothesis testing using partial correlation, multiple correlations, and F test with multiple regression analysis. The results showed that: (1) Student learning facilities and learning motivation had a positive and significant impact on the technical drawing learning outcomes; (2) learning facilities have a positive and significant impact on the technical drawing learning outcomes; (3) and learning motivation has a positive and significant impact on the technical drawing learning outcomes.